Perencanaan Dan Analisis Struktur Baja Menara Pandang Pada Kawasan Wisata Sejuta Pohon Kelapa Di Kabupaten Kuningan - Roesdiana, Tira; Fernando, Tedy (Jurnal Konstruksi dan Infrastruktur : Teknik Sipil dan Perencanaan, 2025)
This research focuses on the structural design and performance analysis of a steel observation tower intended as a supporting facility at the Sejuta Pohon Kelapa tourism area in Kuningan, West Java. The objective is to develop a structurally safe, durable, and efficient observation tower that functions as an iconic landmark enhancing the site’s tourism potential. The study adopts the standards of SNI 1729:2020 (Structural Steel Design), SNI 1726:2019 (Seismic Resistance), and SNI 1727:2020 (Minimum Design Loads) to ensure compliance with national building codes.The research methodology integrates site investigation, data collection, and finite element-based structural analysis. The main structural components analyzed include the composite floor system (bondex slab), secondary and primary beams, columns, and bore pile foundations. The structural design employs WF 200×200×8×12 and WF 300×300×10×15 profiles for the beams and WF 400×400×13×21 for the columns, using BJ41 steel grade. The bore pile foundation system, consisting of four 30 cm diameter piles with a 1.5 × 1.5 × 0.5 m pile cap, is verified to safely resist axial, shear, and moment loads.The analysis results confirm that all structural members satisfy the strength, stiffness, and serviceability requirements according to the applied SNI standards. The overall system demonstrates adequate lateral stability under seismic loading and sufficient bearing capacity in the foundation. Consequently, the proposed steel tower design is structurally feasible, seismically resistant, and suitable for implementation as a sustainable tourism infrastructure that integrates engineering safety with environmental aesthetics.